Host range determination in a novel outbreak pest of sugarcane, Cacosceles newmannii (Coleoptera: Cerambycidae, Prioninae), inferred from stable isotopes. (24th March 2021) - Smit, Chantelle; Javal, Marion; Conlong, Desmond E.; Hall, Grant; Terblanche, John S.
Abstract: An outbreak of Cacosceles newmannii (Coleoptera: Cerambycidae) was detected for the first time on sugarcane ( Saccharum spp.) in 2015 in KwaZulu‐Natal, South Africa. Although primary host plants of this native species remain unknown, these are central to testing hypotheses concerning the outbreak. We hypothesized that this species has undergone a host plant shift (i.e. a feeding association with a novel host plant). We compared δ 13 C and δ 15 N ratios of adult beetles retrieved from South African museum collections, collected between 1891 and 2016 ( n  = 23; 'pre‐outbreak'), with samples from infested fields in 2017 ( n  = 9, 'post‐outbreak') and in 2019 ( n  = 23, 'post‐outbreak'), as well as diverse, plausible host plants ( n  = 42 samples across 10 species) from infested fields and surrounding patches of indigenous and commercial forest vegetation. We used Bayesian isotope mixing models to infer the relative contribution of the different plants to the diet of C. newmannii . Pre‐outbreak, C3 plants contributed strongly to the larval diet, whereas post‐outbreak, C4 plants were the largest component of their diet. There was some indication of C4 plants contributing to their diet pre‐outbreak. Our results suggest that the outbreak of this polyphagous beetle was not a dramatic host shift but rather a rapid increase in the proportion of C4 plants already in their diet. We concluded that plants from the families Fabaceae and Poaceae are the most likely host plants of this species. Nevertheless, the drivers of this rapid outbreak on sugarcane remain poorly determined and should be the focus of future research. Abstract : Image of a male adult Cacosceles newmannii beetle used to infer host plants through body stable isotope measurement